2016
DOI: 10.1074/jbc.m115.704791
|View full text |Cite
|
Sign up to set email alerts
|

A Protein-derived Oxygen Is the Source of the Amide Oxygen of Nitrile Hydratases

Abstract: Nitrile hydratase metalloenzymes are unique and important biocatalysts that are used industrially to produce high value amides from their corresponding nitriles. After more than three decades since their discovery, the mechanism of this class of enzymes is becoming clear with evidence from multiple recent studies that the cysteine-derived sulfenato ligand of the active site metal serves as the nucleophile that initially attacks the nitrile. Herein we describe the first direct evidence from solution phase catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Nature provides nitrile hydratases, which are metallo-enzymes that combine the activation of the nitrilo substrate by coordination to Fe III or Co III to the attack of a coordinated sulfenate (derived from a cysteine residue) on either the water molecule (thus acting as an internal base) 37 , 38 or directly onto the substrate. 39 Although the biomimetic approach has led to the synthesis of a great variety of metal complexes, a relatively small number has been reported as active catalysts for the hydration of acetonitrile. 40 – 42 With mononuclear Co III complexes based on tetraaza ligands, simultaneous coordination of the nitrile and water molecules in the cis -position has been proposed to explain the efficiency of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Nature provides nitrile hydratases, which are metallo-enzymes that combine the activation of the nitrilo substrate by coordination to Fe III or Co III to the attack of a coordinated sulfenate (derived from a cysteine residue) on either the water molecule (thus acting as an internal base) 37 , 38 or directly onto the substrate. 39 Although the biomimetic approach has led to the synthesis of a great variety of metal complexes, a relatively small number has been reported as active catalysts for the hydration of acetonitrile. 40 – 42 With mononuclear Co III complexes based on tetraaza ligands, simultaneous coordination of the nitrile and water molecules in the cis -position has been proposed to explain the efficiency of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The LS state plays an important role in the binding and activation of nitrile substrates and to maintain the LS state, oxidized thiolate ligands are very crucial (Martinez et al, 2014). A recent report further proved that the posttranslational sulfonate acts as the nucleophile that initially attacks the nitrile, and found the source of the product carboxamide oxygen is from the protein (Figure 3D; Nelp et al, 2016). Further quantum mechanics investigation identified that the nitrile hydration reaction evolves toward the product in only three steps.…”
Section: Catalytic Mechanism Of Nhasementioning
confidence: 94%
“… This unique chemistry was subsequently corroborated by time-resolved X-ray crystallography and DFT calculations. , Salient features of this mechanism include (i) direct coordination of the nitrile substrate to the active site metal center , and (ii) activation of the bound nitrile bond toward nucleophilic attack by the αCys–OH ligand, forming a cyclic intermediate ( I in Figure ). Subsequent 16/18 O mass spectrometric studies found that the product amide oxygen is protein-, rather than water-derived, providing further support for active participation by the sulfenic acid (αCys–OH) ligand. Once the cyclic intermediate is formed, it must react with H 2 O to generate the amide product, and two possible pathways have been proposed for this portion of the catalytic mechanism (Figure ).…”
Section: Introductionmentioning
confidence: 99%